Improvement of memory deficits via acetylcholinesterase inhibitory activity of Nepeta nuda ssp. nuda essential oil in rats - Akbaba, Emel; Bagci, Eyup; Hritcu, Lucian; Maniu, Calin (Kuwait Journal of Science, 2021)
Nepeta L. (Lamiaceae) species have been widely used in traditional medicine. Many biological activities of Nepeta species have been reported. In this study, memory enhancing activities of Nepeta nuda ssp. nuda essential oil was aimed to be evaluated in laboratory rats treated scopolamine. Characterization of the oil was carried out by GC-MS/GC-FID system. Memory performances of the rats were evaluated by Y-maze and radial-arm maze tasks. In vitro acetylcholinesterase enzyme activity and molecular docking analysis were also performed in this study. In total, 44 different compounds were identified in Nepeta nuda ssp. nuda essential oil. Trans-cis nepetalactone was showed to be the major compound in the oil. The essential oil, increased spontaneous alternation behaviour in Y-maze task and decreased working memory errors and reference memory errors in radial-arm maze task in scopolamine treated rats as compared to scopolamine alone-treated rats. The oil also showed acetylcholinesterase inhibitory activity in vitro. Molecular docking method, in the mean time, revealed some of the compounds in the oil could interact to acetylcholinesterase enzyme, theoretically. Nepeta nuda ssp. nuda essential oil improved spatial memory of scopolamine-induced rats. Neuroprotective effects of the oil are probably related to anti-cholinesterase activity of the oil. Therefore, Nepeta nuda ssp. nuda essential oil could be used as a complementary therapy to improve memory in neurological diseases like Alzheimer’s disease.